Impact of Online Nursing Education: Nursing Students’ Knowledge Towards Patient Safety in Nursing Academic Institution, Kolkata, West Bengal, India - Jharna Ghosh; Santhna Letchmi Panduragan; Faridah Mohd. Binti Said (International Journal of Community Health Nursing And Practices, 2024)
Introduction: Online education is rapidly growing as an alternative way of preparing nursing students since the COVID-19 pandemic outbreak. The future healthcare workforce has shifted to an online mode of education. Objectives: To assess the impact of online nursing education and nursing students’ knowledge on patient safety. Method: A descriptive study was done among 209 nursing students using a random sampling technique. Data were collected from demographic information on online education and a self-reported knowledge questionnaire. Results: The data revealed that third year (50.72%) and fourth year (49.28%) B.Sc. Nursing students who attended more than 6 months of online classes (55.98%) were from rural residences (67.46%) and faced problems with education material storage (58.85%) and the internet (68.90%). As per opinion, 91.87% students shared that they needed more practice. Data also highlighted that nursing students' (75.12%) knowledge score towards patient safety was very good, with a mean of 24.83, median of 15.68, and SD of 5.49.
Keywords: Knowledge; Online nursing education; demographic data; nursing students; patient safety